HUBUNGAN ANTARA KEBIASAAN BEROLAHRAGA TERHADAP BENTUK POSTUR TUBUH SISWA KELAS VI SD NEGERI 87 KOTA JAMBI - Ahmad Fardiansyah; Endarman Saputra; Mhd.Usni Zamzami Hasibuan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the relationship between exercise habits and body posture of sixth-grade students at SD Negeri 87 Jambi City. The research employed a quantitative approach with a descriptive correlational design. The population consisted of all sixth-grade students totaling 40 participants, and the sampling technique used was total sampling, in which the entire population was selected as the research sample. The research instruments included a questionnaire on exercise habits consisting of 10 items covering the indicators of frequency, duration, intensity, and type of exercise, as well as a body posture observation sheet using the Plumb Line method. The validity test showed that all questionnaire items were valid with r-count values greater than r-table (0.312), while the reliability test obtained a Cronbach’s Alpha value of 0.664 indicating that the instrument was reliable. The descriptive analysis results showed that students’ exercise habits were mostly in the moderate category with 25 students (62%) and in the high category with 15 students (37%). Meanwhile, the results of the body posture observation indicated that 22 students (55%) had normal posture and 18 students (45%) had mild postural deviations. The normality test using Shapiro–Wilk showed that the data were not normally distributed (Sig. 0.001 < 0.05); therefore, the analysis was continued using the Spearman Rank correlation test. The correlation test result showed a significance value of 0.019 (<0.05) with a correlation coefficient of -0.368, which falls into the low correlation category with a negative direction. This indicates that there is a significant relationship between exercise habits and students' body posture. The better the students’ exercise habits, the better their body posture condition.